2014
DOI: 10.1016/j.surg.2014.04.030
|View full text |Cite
|
Sign up to set email alerts
|

A principal component analysis of postinjury viscoelastic assays: Clotting factor depletion versus fibrinolysis

Abstract: Introduction The mechanisms driving trauma-induced coagulopathy (TIC) remain to be defined and its therapy demands an orchestrated replacement of specific blood products. Thrombelastography (TEG) is a tool to guide the TIC multicomponent therapy. Principal component analysis (PCA) is a statistical approach that identifies variable clusters, thus, we hypothesize that PCA can identify specific combinations of TEG-generated values that reflect TIC mechanisms. Methods Adult trauma patients admitted from Septembe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(56 citation statements)
references
References 26 publications
0
56
0
Order By: Relevance
“…The INR alone cannot distinguish between potential ATC mechanisms. Recent studies employing both conventional (60) and viscoelastic (28) measures suggest, however, that the PT/INR captures the most important type of coagulopathy for adverse trauma outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The INR alone cannot distinguish between potential ATC mechanisms. Recent studies employing both conventional (60) and viscoelastic (28) measures suggest, however, that the PT/INR captures the most important type of coagulopathy for adverse trauma outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, we evaluated two risk-adjusted models for each outcome, differing as to the ATC definition but otherwise containing the same covariates. We selected the two candidate ATC definitions, INR >1.2 or INR >1.5, based on the INR thresholds most frequently used in published literature to define ATC (9, 10, 20-28). We compared the fit of the two competing models for each outcome using the Akaike information criterion (49).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Appreciation that the two components of TIC (hypocoagubility and hyperfibrinolysis) are not necessarily linked (7, 8) warrants a re-evaluation of how to design animal models with the objective of identifying specific TIC phenotypes. We found that tissue injury and shock have opposing actions on clot stability.…”
Section: Discussionmentioning
confidence: 99%
“…Principal component analyses suggest that hyperfibrinolysis does not correlate with impaired clot formation (7, 8). In a human study, patients with non-traumatic cardiac arrest had a high prevalence of hyperfibrinolysis (9).…”
Section: Introductionmentioning
confidence: 99%